Advances in functional magnetic resonance imaging data analysis methods using Empirical Mode Decomposition to investigate temporal changes in early Parkinson's disease. Issue 1 (13th June 2018) - Cordes, Dietmar; Zhuang, Xiaowei; Kaleem, Muhammad; Sreenivasan, Karthik; Yang, Zhengshi; Mishra, Virendra; Banks, Sarah J.; Bluett, Brent; Cummings, Jeffrey L.
Abstract: Introduction: Previous neuroimaging studies of Parkinson's disease (PD) patients have shown changes in whole‐brain functional connectivity networks. Whether connectivity changes can be detected in the early stages (first 3 years) of PD by resting‐state functional magnetic resonance imaging (fMRI) remains elusive. Research infrastructure including MRI and analytic capabilities is required to investigate this issue. The National Institutes of Health/National Institute of General Medical Sciences Center for Biomedical Research Excellence awards support infrastructure to advance research goals. Methods: Static and dynamic functional connectivity analyses were conducted on early stage never‐medicated PD subjects (N = 18) and matched healthy controls (N = 18) from the Parkinson's Progression Markers Initiative. Results: Altered static and altered dynamic functional connectivity patterns were found in early PD resting‐state fMRI data. Most static networks (with the exception of the default mode network) had a reduction in frequency and energy in specific low‐frequency bands. Changes in dynamic networks in PD were associated with a decreased switching rate of brain states. Discussion: This study demonstrates that in early PD, resting‐state fMRI networks show spatial and temporal differences of fMRI signal characteristics. However, the default mode network was not associated with any measurable changes. Furthermore, by incorporating an optimum window size in a dynamic functional connectivity analysis, we found altered whole‐brain temporal features in early PD, showing that PD subjects spend significantly more time than healthy controls in a specific brain state. These findings may help in improving diagnosis of early never‐medicated PD patients. These key observations emerged in a Center for Biomedical Research Excellence–supported research environment.